PENGARUH KONEKSI POLITIK, KOMISARIS OTONOM, KOMITE AUDIT DAN UKURAN PERSEROAN PADA AUDIT FEE - Adji, Andik Purnomo (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The determination of the auditor's remuneration is not regulated by a clear law and still refers to the agreement between the auditor and the client. The purpose of this study is to partially and simultaneously examine the impact of political connections, Otonomt commissioners, audit committees and company size on audit fees. The study was conducted using a quantitative approach. The study population was drawn from companies included in the Jakarta Islamic Index in 2018-2021 and a sample of 20 companies was obtained using the targeted sampling method. The analysis method used is a multiple linear regression analysis using SPSS v23 software. Findings of this study: (1) Partially political connections, Otonomt commissioners, audit committees do not have a significant impact on audit fees. Meanwhile, the size of the company partially has a significant impact on the cost of the audit. (2) Political connections, Otonomt commissioners, audit committees, and company size simultaneously have a significant impact on audit fees.